СОВРЕМЕНИ ПРОМЕНИ ВО МАКЕДОНСКИОТ СТАНДАРДЕН ЈАЗИК (Philological Studies, 2019)
The article has as main subject the current situation regarding the status and corpus of texts about Macedonian language. The analysis comprises the status of Macedonian in the Constitution and several laws concerning the usage of Macedonian and other languages spoken in Macedonia. Several aspects are taken in consideration: the standardization process, the status of Macedonian language after 1991 when Republic of Macedonia became an independent state, the conflict of 2001 and the constitutional amendments in 2002. In the second section, some linguistic features are analysed, such as: tendencies in the accent and formation of accentual units, morphological and syntactic characteristics, as well as the lexicon and the tendencies of language borrowing. Regarding the lexicon, there is a significant layer of Anglicisms which is present primarily in publicistic and administrative style, as well as in colloquial language. In this regard, in the domain of language planning, it is primarily important to make a systematic approach to this lexicon and its functional use in different styles. Also, it is indispensable to modify and/or rectify certain orthographic rules in regard to transcription and transliteration of English, as well as the linguistic adaptation of Anglicisms in Macedonian.